Pembuatan Bioetanol Dari Kulit Buah Nanas Dengan Metode Solid State Fermentation (SSF) Dan Pemurnian Dengan Proses Distilasi-Adsorbsi Dengan Variasi Ratio Bioetanol:Adsorben - Safitri, Nadira; Chairul, Chairul; Amraini, Said Zul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Bioethanol is an ethanol which can be obtained by glucose fermentation from carbohydrate source that uses microorganisms help continued by distillation process. Adsorption is a separation process where the components of a fluid phase moves to the absorbing surface of the solid (adsorbent). In the fermentation process pineapple peel waste with Zymomonas mobilis and distillation process obtained the highest ethanol content of 11%, ethanol content obtained is not too high, so it needs a process that can increase the purity of bioethanol with distillation adsorption process. Bioethanol purification process using natural zeolite as adsorbent with variable change is the type of adsorbent of natural zeolite without activation with base activated natural zeolite and bioethanol:adsorbent ratio is 1:0,35 ; 1:0,5 ; 1:0,65. From the experimental results indicated that the highest ethanol content obtained of the zeolite and ethanol massa ratio of 1:0,65 with using base activated natural zeolite, ethanol content of 99,8% which fulfill Indonesian National Standard (SNI) for both technical ethanol and denatured bioethanol specification. Keywords : bioethanol, solid state fermentation, pineapple peel, distillation adsorption, natural zeolite